Hegemonic regulations of kinship: gender and sexualities norms in Italy - Lasio, Diego (2019)
After many years of heated debate, in 2016 the Italian parliament passed a law to regulate same-sex civil unions. Although the law extends to same-sex couples most of the rights of married heterosexual couples, the law preserves legal differences between heterosexual marriage and same-sex civil unions; moreover, the possibility of a partner in a same-sex couple adopting the biological children of the other partner was so controversial that it had to be deleted in order for the law to pass. The research project presented in the present thesis aimed at understanding which discourses and social practices are currently used in Italy by heteronormativity to resist challenges to the hegemonic model of kinship. Three studies have been carried out for this purpose, respectively focused on: 1) the public debate that occurred in Italy while the law proposal was under discussion in parliament; 2) the speeches of the Members of Parliament (MP) who opposed the section of the bill concerning lesbian and gay parenthood; 3) the discourses of Italian LGBT activists about lesbian and gay parenting. The analyses highlight that the opposition to the recognition of gay and lesbian couples and their children contributes to maintain the hegemonic gender order and to reiterate restrictive standards of motherhood. Traces of heteronormativity are also present in the discourses of LGBT activists, namely in terms of access to reproduction, the parents’ place within the regime of gender and the right standards for childrearing. Theoretical and practical implications of these discourses are discussed.